Help seeking behavior of children during peer conflict - Santos, Jennifer B (2007)
Help seeking behavior of children in the face of peer conflict was investigated. Twenty 8-year-old students and twenty 10-year-old students from a co-ed government school were observed in order to document peer conflicts encountered in school. Vignettes were developed (based on observation data) and administered to determine whether children's age, gender,and presence/absence of onlookers were associated white children's decision to seek help from the teacher during peer conflict help. Observations revealed that 10-year old girls would seek help from the teacher when when instrumental conflicts were involved, while 10-year-olf boys would seek help during physical and rule violation conflicts. They were also inclined to go the teacher if the aggressor was perceived to be physically bigger. Presence of onlookers would make girls seek help. Boys on the other hand would seek help in the absence of onlookers. Interview of 8 and 10-year old students disclosed that majority opted not to seek help from teachers because they think they could settle the conflict by themselves. Observation and vignette data for the 8-year-old group were not available because no conflict was manifested during observation.